Anti-tumour necrosis factor treatment for the prevention of ischaemic events in patients with deficiency of adenosine deaminase 2 (DADA2). (9th January 2021) - Cooray, Samantha; Omyinmi, Ebun; Hong, Ying; Papadopoulou, Charalampia; Harper, Lorraine; Al-Abadi, Eslam; Goel, Ruchika; Dubey, Shirish; Wood, Mark; Jolles, Stephen; Berg, Stefan; Ekelund, Maria; et al.
Abstract: Objective: To evaluate the impact of anti-Tumour Necrosis Factor-α (anti-TNF) treatment on the occurrence of vasculitic ischaemic events in patients with deficiency of adenosine deaminase 2 (DADA2). Methods: A retrospective analysis of DADA2 patients referred from six centres to Great Ormond Street Hospital for Children was conducted. Ischaemic events, vasculitic disease activity, biochemical, immunological, and radiological features were compared, before and after anti-TNF treatment. Results: A total of 31 patients with genetically confirmed DADA2 were included in the study. The median duration of active disease activity prior to anti-TNF treatment was 73 months (inter-quartile range [IQR] 27.5–133.5 months). Twenty seven/31 patients received anti-TNF treatment for a median of 32 months (IQR 12.0–71.5 months). The median event rate of central nervous system (CNS) and non-CNS ischemic events before anti-TNF treatment was 2.37 per 100 patient-months (IQR 1.25–3.63); compared with 0.00 per 100 patient-months (IQR 0.0–0.0) post-treatment ( p < 0.0001). Paediatric vasculitis activity score (PVAS) was also significantly reduced: median score of 20/63 (IQR 13.0–25.8/63) pre-treatment vs. 2/63 (IQR 0.0–3.8/63) following anti-TNF treatment ( p < 0.0001), with mild livedoid rash being the main persisting feature. Anti-TNF treatment was not effective for severe immunodeficiency or bone marrow failure, which required haematopoietic stem cell transplantation (HSCT). Conclusion: Anti-TNF treatment significantly reduced the incidence of ischaemic events and other vasculitic manifestations of DADA2, but was not effective for immunodeficiency or bone marrow failure.